SIMULATION OF A GROUND PROCESSING UNIT WITH THE DEVELOPMENT OF RECOMMENDATIONS FOR THE SELECTION OF WORKING BODIES - HUNKO, Iryna; HRYBYK, Roman (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The paper provides a mathematical rationale for selecting the number of working bodies of the combined tillage unit depending on the physical and mechanical parameters of the soil, the topography of the field, agrotechnical requirements for sowing and planting agricultural crops, ecological and energy indicators of pre-sowing tillage operations. Improving the quality of terrain use, soil compaction, reducing energy costs, and improving environmental performance during pre-sowing cultivation can be achieved by determining the optimal combination of working bodies in a combined tillage unit. As a rule, pre-sowing treatment is carried out in the state of physical maturity of the soil and in the shortest possible time, not allowing a gap between pre-sowing treatment and sowing, as this leads to loss of soil moisture and a decrease in yield. It has been established that a one-day delay in closing moisture leads to unproductive moisture losses and reduced yield. Therefore, closing moisture is an extremely urgent component of a complete system of pre-sowing field cultivation. In order to protect the soil from excessive destruction and compaction (and, therefore, to preserve moisture in it), the optimal solution is to carry out only one working pass of the equipment immediately before sowing. At the same time, the combined action of various working bodies can both increase and reduce the total traction resistance of agricultural machinery, so the final choice of the composition of the working bodies and the width of the grip can be made only on this basis. Results of field studies of the test model. Based on the analysis of the structure of the tillage unit, a structural and technical drawing of a multifunctional tillage unit with a variable working body for tractors from 90 to 340 hp is presented. for forming a seed bed and leveling the ground. A thin sowing layer of blocks thanks to the optimal combination of arrow jaws, lamellas and ring tips in the machine. Recommendations on the composition of joint farms have been developed.